2014
DOI: 10.1177/0971721813514265
|View full text |Cite
|
Sign up to set email alerts
|

A Survey on Nanotechnology in the View of the Turkish Public

Abstract: There is considerable interest in public understanding of emerging technologies because public understanding can have an important effect on the implementation of these technologies. Although there are many studies that have focused on public understanding of nanotechnology, no studies on this topic have been conducted in the Turkish public. Therefore, this study was conducted to reveal the status of the Turkish public’s perception of nanotechnology. A survey, including several items that assessed Turkish publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
9

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 32 publications
1
4
0
9
Order By: Relevance
“…Optimism regarding the application of nanotechnology in general has been reported in Iran (Farshchi, Sadrnezhaad, Nejad, Mahmoodi, & Abadi, 2011). Similar results were reported for high school students (Sahin and Ekli (2013) and adults (Senocak, 2014) in Turkey. In India, which has invested in nanotechnology, however, there is little activity focused on understanding public attitudes and priorities, despite exten-sive scientific research activity being conducted (Jayanthi, Beumer, and Bhattacharya (2012).…”
Section: Public Attitudes Towards Nanotechnology As An Enabling Technsupporting
confidence: 80%
“…Optimism regarding the application of nanotechnology in general has been reported in Iran (Farshchi, Sadrnezhaad, Nejad, Mahmoodi, & Abadi, 2011). Similar results were reported for high school students (Sahin and Ekli (2013) and adults (Senocak, 2014) in Turkey. In India, which has invested in nanotechnology, however, there is little activity focused on understanding public attitudes and priorities, despite exten-sive scientific research activity being conducted (Jayanthi, Beumer, and Bhattacharya (2012).…”
Section: Public Attitudes Towards Nanotechnology As An Enabling Technsupporting
confidence: 80%
“…Similarly, in Enil and Köseoğlu's study (2016), it was concluded that teacher candidates mostly acquire information about nanotechnology from radio and Tv programs. In most studies, it has been observed that awareness of nanotechnology has not been created and individuals have insufficient knowledge about it (Elmarzugi et al,2014;Enil and Köseoğlu, 2016;Şenocak, 2014). It may be beneficial to have visual and written media support or to use social media which has become popular in recent times to create awareness in individuals and increase their general knowledge level on nanotechnology.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Benzer şekilde Enil ve Köseoğlu (2016) araştırmalarında öğretmen adaylarının Nanoteknoloji ile ilgili ilk bilgilerini daha çok radyo ve TV programlarından edindikleri sonucuna ulaşmışlardır. Yapılan araştırmaların çoğunluğunda Nanoteknoloji konusunda bir farkındalığın oluşmadığı ve bireylerin bu konuda yeterince bilgi sahibi olmadıklarıdır (Elmarzugi vd.,2014;Enil ve Köseoğlu, 2016;Şenocak, 2014). Bireylerde bu konu ile ilgili farkındalık oluşturmak ve genel bilgi düzeylerini arttırabilmek için görsel medya desteği yararlı olabilir.…”
Section: Tartişma Sonuç Ve öNeri̇lerunclassified
“…İşbirlikli öğrenme yöntemiyle, üç ile altı hafta arasında değişen farklı süreçlerde uygulanmış fen ve kimya alanındaki çalışmalarda da akademik başarının artışı, bu çalışmada elde edilen sonuçlar ile uyuşmaktadır (Doymuş, 2008a;Karaçöp, Doymuş, Doğan ve Koç, 2009;Şimşek, Doymuş, Doğan ve Karaçöp, 2009;Bilen, 2011;Kılınç ve Güven Yıldırım, 2015). (Elmarzugi vd.,2014;Enil ve Köseoğlu, 2016;Şenocak, 2014). Bireylerde bu konu ile ilgili farkındalık oluşturmak ve genel bilgi düzeylerini arttırabilmek için görsel medya desteği yararlı olabilir.…”
Section: Tartişma Sonuç Ve öNeri̇lerunclassified